Caracterización de manglares de Centroamérica con sensores remotos - Lizano, Omar G. (2001)
Satellite images were used to study the mangrove distribution patterns in two different climatic regions of Central America: Gulf of Fonseca in Honduras-El Salvador and Sierpe-Térraba in Costa Rica. The Gulf of Fonseca has higher temperature and solar radiation, and lower precipitation, which can explain the higher structural development and species mixing of the Sierpe-Térraba mangrove. In the latter the transition between species or between heights in the same species is clear. The automatic classification made by the Geographic Information System (IDRISI) fits well the field mangrove distribution, but it was necessary to regroup some subdivisions that represent the same land use as identified by transects and an aerial video. Mixed species and clouds produced less satisfactory results in Sierpe-Térraba indicating a need for better satellite image resolution.